Achieving Gender Equality and Women's Empowerment in Sub-Saharan Africa: Lessons from the Experience of Selected Countries. Issue 2 (June 2019) - Moyo, Theresa; Dhliwayo, Rogers
Despite the progress that has been made towards achieving gender equality and the empowerment of women and girls in sub-Saharan Africa (SSA), evidence shows that gender disparities remain persistent in most countries. The aim of the article is to identify lessons from the experiences of those countries which have made considerable progress in bridging the gender gap. More specifically, the article seeks to identify strategies that will enable SSA countries to achieve the gender equality goal in the United Nations 2030 Agenda for Sustainable Development.